BREAST MILK PRODUCTION AND DETERMINING FACTORS - Mastina; Lestari, Siti (Jurnal Smart Kebidanan, 2025)
Good maternal nutrition and exclusive breastfeeding, optimal nutrition for infants and toddlers is important for good growth and development, this can reduce the risk of non-communicable diseases (NCDs) for both mothers and children. The purpose of this study is This study aims to determine the relationship between the nutritional status of breastfeeding mothers and breast care with the adequacy of breast milk. Cross-sectional research design. The population is 74 people. The sampling technique uses Purposive Sampling. The number of samples is 34 breastfeeding mothers. The results of the study showed that there was a relationship between food variation and breast care with the adequacy of breast milk with a p-value of 0.000. and there is a relationship between breast care with the adequacy of breast milk with a p-value of 0.003. Conclusion Breastfeeding mothers need a variety of foods and good breast care, the growth and development of babies are supported by good nutritional intake. Suggestions provide a variety of nutritious foods and carry out routine breast care for breastfeeding mothers.